United Nations General Assembly Resolution and Its Implementation by Non-Governmental Organizations: A Review of Situation in Rakhine Myanmar - Ainna Khairunnisa; Muhammad Ya'kub Aiyub Kadir (Student Journal of International Law, 2021)
The UN General Assembly has adopted several resolutions in response to the Myanmar human rights situation, including the resolution A/RES/74/246 of 2019. One of the key players to implement the UNGAR is the Non-Governmental Organizations (NGOs). However, the international legal standing of the NGOs has not yet been clearly established. Herein, Article 71 of the UN Charter has been acted as the basis of NGO operation. This research aims to examine the eligibility of Article 71 of the UN Charter to provide legal standing for NGOs operation and to investigate the contributions of NGOs to the implementation of UNGAR 74/246. The research employed normative-empirical method. The result showed that the article does not clarify international legal standing of NGOs operation. However, the NGOs has played its role as mandated by the UNGAR. It is recommended to implement the future agenda on NGOs legal standing in order to support their contribution.